Reconstitution of the recombinant RanBP2 SUMO E3 ligase complex - Ritterhoff, Tobias; Das, Hrishikesh; Hao, Yuqing; Sakin, Volkan; Flotho, Annette; Werner, Andreas; Melchior, Frauke (SUMO, 2016)
One of the few proteins that have SUMO E3 ligase activity is the 358 kDa nucleoporin RanBP2 (Nup358). While small fragments of RanBP2 can stimulate SUMOylation in vitro, the physiologically relevant E3 ligase is a stable multi-subunit complex comprised of RanBP2, SUMOylated RanGAP1, and Ubc9. Here, we provide a detailed protocol to in vitro reconstitute the RanBP2 SUMO E3 ligase complex. With the exception of RanBP2, reconstitution involves untagged full-length proteins. We describe the bacterial expression and purification of all complex components, namely an 86 kDa His-tagged RanBP2 fragment, the SUMO E2-conjugating enzyme Ubc9, RanGAP1, and SUMO1, and we provide a protocol for quantitative SUMOylation of RanGAP1. Finally, we present details for the assembly and final purification of the catalytically active RanBP2/RanGAP1*SUMO1/Ubc9 complex.